Charisma in conservation biology. Preliminary notes to an aesthetic-philosophical approach (Itinera, 2025)
The aim of this paper is to explore the notion of charisma in conservation biology.In recent years, this notion has become very popular among conservationists, for example in the expression “charismatic megafauna.” In general, in conservation biology, species are described as “charismatic” when they exert a non-ordinary impact on humans – specifically in their capacity to capture attention, engage the imagination, and evoke memorable emotional responses.Despite its widespread usage, the notion of charisma has, with few exceptions, received limited critical scrutiny so far from a conceptual and philosophical standpoint within the conservation sciences.This paper sets out to begin that task, by returning to the Weberian origin of the concept and putting forward an interpretation of non-human charisma as an emergent, relational, context-dependent, and ecologically collective phenomenon.
Keywords: extinction; bias; Anthropocene; Max Weber